Mastering Sentence Structure and Interest in Writing and its Relationship with Expository Writing Ability of Class VIII Students in SMPN 5 Bandar Lampung - Suliyana Suliyana; Supriyono Supriyono; Joko Sutrisno AB; Dian Windriani (IJLHE: International Journal of Language, Humanities, and Education, 2020)
This study aims to describe the relationship between sentence structure mastery and writing interest with the ability to write exposition in class VIII SMPN 5 Bandar Lampung. This study uses correlational method; it means that data is collected after all the events happen. The test and questionnaire are chosen as the technique in taking the research data. Data analysis or hypothesis testing uses the product moment and multiple correlation coefficient formulas. The results of this study show that 1) there is a positive and significant relationship between sentence structure mastery and the ability to write exposition, indicated by the correlation coefficient of 0.772 and the coefficient of determination (r2) of .596 or 59.69%, 2) there is a positive and significant relationship between writing interest and expository writing ability as indicated by a correlation coefficient of 0.713 and a coefficient of determination (r2) of 0.508 or 59.80%.